COMUNICACIÓN ORGANIZACIONAL Y REPUTACIÓN DIGITAL EN ORGANIZACIONES PRIVADAS Y DEL TERCER SECTOR DE MÉXICO Y ESPAÑA - Dra. HERLINDA ORTIZ RODRÍGUEZ (Fonseca, Journal of Communication, 2023)
Corporate reputation is a fundamental intangible resource for any type of organization to establish bonds of trust with their audiences. Its management must be distributed into different spaces, with strategies and communication tools according to the audiences’ requirements. Due to the emergence of internet, online reputation has appeared as an important space for corporate reputation management, introducing new challenges to the organizations in their digital communication.